A coating type double network hydrogel coating and its preparation method and application
By forming a dual network structure in polyzwitterionic hydrogel, the combination of κ-carrageenan, metal ion and acrylic monomer zwitterionic monomers is solved, and the problem of insufficient mechanical properties of the hydrogel is achieved in the marine defense Efficient anti-fouling and anti-bacterial and anti-protein effects in the pollution field.
Patent Information
- Application Number
- CN202310801818.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-06-30
AI Technical Summary
Poor mechanical properties of polyzwitterionic hydrogel materials have resulted in limited applications in the field of marine anti-fouling, and existing improved methods have failed to meet the requirements of marine anti-fouling.
Kappa-carrageenan is used to form a first crosslinking network with metal ions, and a second crosslinking network is formed through acrylic monomers and zwitterionic monomers to form a dual network structure to enhance the mechanical properties of the hydrogel and anti-fouling and resistance reduction performance.
The mechanical properties of the hydrogel are significantly improved, with a fracture stress reaching 1.98MPa, an elongation of break of up to 1171%, and a Young's modulus of 2.03MPa, which has excellent anti-fouling and anti-bacterial and anti-protein adsorption effects.
Smart Images

Figure CN116875101B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a coating type double network hydrogel coating and a preparation method and application thereof. Background Art
[0002] Marine sessile organisms (such as barnacles, algae, and sea squirts) tend to adhere to hard solid surfaces but have no adhesion to soft and water-rich surfaces, such as seaweed, fish, and jellyfish. Hydrogel is a soft material with high water content. Polyzwitterionic hydrogel is a network hydrogel formed by polymerization and cross-linking of zwitterionic compounds. Each structural unit of the polymer carries a pair of oppositely charged charges and has a very high density of ionic groups. Therefore, the molecular chain has a strong hydrophilicity and can form a dense hydration layer on its surface. It has broad application prospects in the field of marine antifouling.
[0003] However, the disadvantages of polyzwitterionic hydrogel materials are equally significant. During the preparation of hydrogels, the non-uniformity of gelation will lead to an uneven gel network structure, and there will be randomly distributed hanging chains, long and short chains, etc. in the hydrogel; when the hydrogel is subjected to force, the microscopic stress will be transmitted along the polymer chain to the short chain and other structural weak points, resulting in local stress concentration and molecular chain breakage, which is manifested macroscopically as crack generation and overall rupture. In addition, the density of polymer chains in hydrogels is low and the intermolecular interactions are weak. Once cracks are generated, they are easy to expand rapidly and lead to macroscopic rupture. The shear modulus of pure polyzwitterionic hydrogel is only about 1kPa, and the tensile fracture deformation is only 11%. The poor mechanical strength seriously hinders the application of this type of hydrogel in the field of marine antifouling.
[0004] In order to improve the mechanical strength of polyzwitterionic hydrogels, researchers have made many attempts. For example, the Chinese patent document with publication number CN115260529A discloses a method for preparing a high-performance, low-friction nanocomposite hydrogel. The invention improves the mechanical properties of pure PSBMA (polymethylsulfobetaine) hydrogel by introducing Ti3C2. Ti3C2 is a two-dimensional material MXene. Through free radical polymerization and physical electrostatic adsorption, it forms an interwoven nanocomposite hydrogel network with SBMA. However, the tensile strength of the product hydrogel produced by the invention is still below 1MPa, which cannot meet the requirements for marine antifouling use.
[0005] A Chinese patent document with publication number CN105295073A discloses a method for preparing a highly flexible zwitterionic hydrogel. The invention obtains a highly flexible zwitterionic SBMA hydrogel by improving the concentration of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide monomer, crosslinker and initiator. The zwitterionic SBMA hydrogel has better tensile and compressive properties than traditional SBMA hydrogels and is more suitable for the field of biomedical engineering rather than marine antifouling.
[0006] Therefore, how to effectively improve the mechanical properties of polyzwitterionic hydrogels and use a simple coating process to form a hydrogel coating to improve the application value of polyzwitterionic hydrogels in the field of marine antifouling remains to be solved. Summary of the invention
[0007] In order to solve the problem of poor mechanical properties of existing polyzwitterion hydrogel materials, the present invention provides a coated double-network hydrogel coating, which has a structure in which a first cross-linked network and a second cross-linked network penetrate each other, has excellent mechanical properties, good hydrophilicity, and good anti-fouling and drag reduction properties.
[0008] The specific technical solutions adopted are as follows:
[0009] A coating type double network hydrogel coating, the coating type double network hydrogel coating is made of κ-carrageenan, metal ions, acryl monomers, zwitterionic monomers, photoinitiators, and crosslinking agents; wherein, after sol-gel transformation, the κ-carrageenan forms a first crosslinking network through coordination with the metal ions, and the acryl monomers and zwitterionic monomers form a second crosslinking network through free radical polymerization under the action of the photoinitiator and the crosslinking agent; the coating type double network hydrogel coating has a double network structure formed by the first crosslinking network and the second crosslinking network interpenetrating each other.
[0010] As mentioned above, the main reasons for the poor mechanical properties of existing polyzwitterionic hydrogel materials include the following two points: (1) the internal network structure of the hydrogel is uneven; (2) the polymer content is low and there is a lack of effective energy dissipation mechanism. The present invention designs a coated double network hydrogel coating with excellent mechanical properties by improving the toughness of the molecular chain itself, making the network structure more uniform, improving the cross-linking structure to reduce stress concentration, or introducing an effective energy dissipation mechanism.
[0011] The present invention uses natural and readily available κ-carrageenan and metal ions to prepare the first cross-linked network, through the double helical aggregate structure of κ-carrageenan itself and the metal ions (preferably Zr 4+) has a strong coordination effect, forming an effective energy dissipation mechanism and improving the mechanical properties of the hydrogel; the second cross-linked network is prepared by using propylene monomers and zwitterionic monomers. The propylene monomer plays the role of toughening and adjusting the component ratio, and the zwitterionic monomer plays the role of high hydrophilicity of zwitterions, which has the effect of anti-fouling and drag reduction; the formation of the double network structure greatly enhances the strength of traditional polyzwitterionic hydrogel materials and inhibits the anti-polyelectrolyte effect of zwitterionic polymers in salt solutions.
[0012] Preferably, the metal ion is Zr 4+ .
[0013] Preferably, the acrylic monomer is acrylamide, acrylamide derivatives, acrylic acid or acrylic acid derivatives.
[0014] The zwitterionic monomer is at least one of the compounds having structural formulas (I) to (IV);
[0015]
[0016] Wherein, R1 is H or methyl; R2 and R3 are independently selected from H or C1-C5 aliphatic hydrocarbon groups; n is an integer of 1-3; Z1 is a benzenesulfonic acid group, a sulfonic acid group, a phosphoric acid group, a benzenesulfonate group, a sulfonate group or a phosphate group; X is H, an alkali metal or an ammonium group; and the structural formula of Y is any one of the following:
[0017]
[0018] Wherein, R4 and R7 are independently selected from C2 to C5 aliphatic hydrocarbon groups, R5, R6, R8 and R9 are independently selected from C1 to C5 aliphatic hydrocarbon groups, R 10 is a C1-C5 aliphatic hydrocarbon group or a phenyl group, J is N or P, and Z2 is a halogen, a sulfonic acid group, a sulfate group, a phosphite group, a monophosphoric acid group or an acetic acid group.
[0019] The photoinitiator is a water-soluble photoinitiator, selected from at least one of 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,2'-azobisisobutylamidine dihydrochloride, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.
[0020] The crosslinking agent is a water-soluble crosslinking agent, selected from at least one of N,N'-methylenebisacrylamide, N,N'-vinylbisacrylamide, hexamethylenebisacrylamide, ethylene glycol diacrylate, dipropylene glycol diacrylate, triethylene glycol dimethacrylate and ethylene glycol dimethacrylate.
[0021] The present invention also provides a method for preparing the coated double-network hydrogel coating, comprising the following steps:
[0022] (1) mixing κ-carrageenan, a second network monomer, a photoinitiator, a crosslinking agent and water to obtain a mixed solution, and heating and dissolving the mixed solution under light-proof conditions to obtain a uniform precursor solution;
[0023] (2) coating the precursor solution onto a substrate, refrigerating and standing under light-proof conditions, taking it out and subjecting it to UV light crosslinking treatment and metal ion solution immersion coordination crosslinking treatment, and further immersing the obtained hydrogel in water to obtain the coated double network hydrogel coating after the size is stable;
[0024] The second network monomers include acrylic monomers and zwitterionic monomers.
[0025] The present invention first prepares a precursor solution containing reaction raw materials, and after coating the precursor solution into a coating, the precursor solution is refrigerated and kept still under light-proof conditions to induce κ-carrageenan to undergo a sol-gel transition, wherein the molecules thereof are transformed from a random coil conformation to a helical conformation, and O-2 and O-6 of galactose between the molecules are twisted into a double helix by hydrogen bonds to generate a binding point of a polymer chain. As the temperature continues to drop, the binding points of the double helix aggregate to form a gel, thereby obtaining a first cross-linked network precursor; in a further ultraviolet light cross-linking treatment process, the propylene monomer and the zwitterionic monomer undergo free radical polymerization to form a second cross-linked network; subsequently, the metal ion solution is immersed in a coordination cross-linking treatment to allow the metal ions and the OSO3 on the κ-carrageenan molecules to bind to each other. - A large number of coordination complexes are formed between the two groups to strengthen the hydrogel. Finally, the residual uncoordinated Zr 4+ , and obtain the coated double-network hydrogel coating.
[0026] Preferably, the mass ratio of the κ-carrageenan to the second network monomer is 0.075-0.15:1; the molar ratio of the second network monomer, the photoinitiator and the crosslinking agent is 1:5×10 -4 -1.5×10 -3 :5×10 -5 -1.5×10 -4 ; In the second network monomer, the molar fraction of the propylene monomer is 60 to 99%, and the molar fraction of the zwitterionic monomer is 1 to 40%; within the above preferred range, sufficient reaction between the monomers and the degree of cross-linking can be guaranteed to obtain a coated double-network hydrogel coating with good hydrophilicity, excellent mechanical properties and good anti-fouling properties.
[0027] Preferably, in step (1), the mixed solution is dissolved at 60-90° C. for 2-6 hours. Heating at too high a temperature may cause premature polymerization of the second network monomer.
[0028] The material of the substrate is a transparent material, including at least one of inorganic glass, polyethylene film, polyester film and polyvinyl chloride film.
[0029] During the refrigerated storage, the κ-carrageenan undergoes a sol-gel transition. Preferably, in step (2), the refrigeration temperature is 0-8°C and the refrigeration time is 12-36 hours.
[0030] Preferably, in step (2), the conditions for ultraviolet light cross-linking are: wavelength 365nm, and cross-linking time is 3-4h.
[0031] Preferably, in step (2), the conditions for the metal ion solution immersion coordination crosslinking are: the metal ion solution is 0.05-0.5M Zr-containing 4+ The immersion time is 36-60h. 4+ The complexation with OSO3- on the κ-carrageenan molecular chain can form a strong metal coordination complex. 4+ The cross-linked enhanced hydrogel not only has excellent mechanical properties, but also remains stable in aqueous solution, which improves the stability of the hydrogel in water and reduces swelling.
[0032] Preferably, in step (2), the soaking time in water is 5-10 days.
[0033] The present invention also provides application of the coated double-network hydrogel coating in the field of marine antifouling.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) During the sol-gel transition of κ-carrageenan, the macromolecular chains transform from random coil conformation to helical conformation and then form a three-dimensional network gel structure. This special double helical aggregate structure can serve as an effective energy dissipation mechanism to prevent the expansion of cracks. Furthermore, metal ions complex with sulfate groups on the κ-carrageenan molecular chains to form strong metal coordination complexes, which can dissipate energy and improve the stability of κ-carrageenan, thus solving the problem that the double helical structure induced by its own hydrogen bonds in κ-carrageenan without coordination is difficult to withstand hydrostatic pressure and swell and dissolve.
[0036] (2) Propylene monomers and zwitterionic monomers are used as the second network monomers, wherein the propene monomer plays the role of toughening and adjusting the component ratio, and the zwitterionic monomer plays the role of high hydrophilicity of zwitterions to achieve the effect of anti-fouling and drag reduction; the second network uses a cross-linking agent to make it present a three-dimensional network structure, further improving the mechanical properties.
[0037] (3) The coated double-network hydrogel coating has a structure in which the first cross-linked network and the second cross-linked network penetrate each other, and has excellent mechanical properties. The breaking stress can reach 1.98MPa, the breaking elongation can reach 1171%, the Young's modulus can reach 2.03MPa, and the hydrophilicity is good. The formation of the double-network structure greatly enhances the strength of the traditional polyzwitterionic hydrogel material and inhibits the anti-polyelectrolyte effect of zwitterionic polymers in salt solutions. When applied to the field of marine antifouling, it can effectively block the attachment of proteins and bacteria and achieve a nonspecific antifouling effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a fluorescence microscope picture of the adsorption and adhesion of Escherichia coli by the coated double-network hydrogel coating prepared in Example 1.
[0039] Figure 2 This is a fluorescence microscope picture of the adsorption and adhesion of Staphylococcus aureus by the coated double-network hydrogel coating prepared in Example 1.
[0040] Figure 3 The statistical results of the ultraviolet absorption peak intensity of the hydrogel coatings prepared in Example 1 and Comparative Example 1 for adsorption and adhesion of bovine serum albumin. DETAILED DESCRIPTION
[0041] The present invention is further illustrated below in conjunction with the examples and accompanying drawings. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0042] Example 1
[0043] (1) 0.9 g of κ-carrageenan, 6.077 g of acrylamide, 1.257 g of dimethylpropyl sulfonamide ethyl methacrylate, and 9 mL of a photoinitiator 2-hydroxy-2-methyl-1-phenyl ketone solution (concentration of 1 × 10 -5 mol / mL), 90 μL N,N'-methylenebisacrylamide solution (concentration of 1×10 -4 mol / mL) was mixed with 21 mL of deionized water to obtain a mixed solution; the mixed solution was heated in a water bath at 70° C. for 3 hours under light-proof conditions to obtain a uniform precursor solution;
[0044] (2) The precursor solution was coated on a glass slide, and allowed to stand at room temperature in the dark for 1 hour, and then placed in a refrigerator at 4°C. After 24 hours, the glass slide was taken out and then placed in a 365 nm double-sided ultraviolet lamp for crosslinking for 3 hours. The glass slide was then placed in a 0.1 M ZrOCl2·8H2O aqueous solution for 48 hours to complete the coordination crosslinking. The obtained hydrogel was further immersed in water for about 1 week, during which the water was changed several times. After the size was stabilized, the coated double network hydrogel coating was obtained.
[0045] Example 2
[0046] (1) 0.9 g of κ-carrageenan, 5.757 g of acrylic acid, 2.514 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-phosphate, and 9 mL of 1-hydroxy-cyclohexyl-phenyl ketone solution (concentration of 1 × 10 - 5 mol / mL), 90 μL of ethylene glycol diacrylate solution (concentration of 1×10 -4 mol / mL) was mixed with 21 mL of deionized water to obtain a mixed solution; the mixed solution was heated in a water bath at 80° C. for 2 hours to obtain a uniform precursor solution;
[0047] (2) The precursor solution is coated on a glass slide, and after standing in the dark at room temperature for 1 hour, it is placed in a refrigerator at a temperature of 0°C, taken out after 12 hours, and then placed in a 365nm double-sided ultraviolet lamp for crosslinking for 3 hours, and then placed in a 0.2M ZrOCl2·8H2O aqueous solution for 40 hours to complete the coordination crosslinking. The obtained hydrogel is further immersed in water for about 1 week, during which the water is changed several times, and the coated double network hydrogel coating is obtained after the size is stable.
[0048] Example 3
[0049] (1) 0.9 g of κ-carrageenan, 5.438 g of methacrylamide, 3.771 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]ethane-1-carboxylic acid inner salt, and 9 mL of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide solution (concentration of 1 × 10 -5 mol / mL), 90 μL hexamethylenebisacrylamide solution (concentration 1×10 -4 mol / mL) was mixed with 21 mL of deionized water to obtain a mixed solution; the mixed solution was heated in a 60° C. water bath for 6 hours to obtain a uniform precursor solution;
[0050] (2) The precursor solution is coated on a polyester sheet, and after standing in the dark at room temperature for 1 hour, it is placed in a refrigerator at 8°C, taken out after 36 hours, and then placed in a 365nm double-sided ultraviolet lamp for crosslinking for 3 hours, and then placed in a 0.05M ZrOCl2·8H2O aqueous solution for 36 hours to complete the coordination crosslinking. The obtained hydrogel is further immersed in water for about 1 week, during which the water is changed several times, and the coated double network hydrogel coating is obtained after the size is stable.
[0051] Example 4
[0052] (1) 0.9 g of κ-carrageenan, 5.118 g of methacrylic acid, 5.028 g of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 9 mL of 2-hydroxy-2-methyl-1-phenylmethanone solution (concentration of 1 × 10 -5 mol / mL), 90 μL of dipropylene glycol diacrylate solution (concentration of 1×10 -4 mol / mL) was mixed with 21 mL of deionized water to obtain a mixed solution; the mixed solution was heated in a 70° C. water bath for 3 hours to obtain a uniform precursor solution;
[0053] (2) The precursor solution was coated on a glass slide, and allowed to stand at room temperature in the dark for 1 hour, and then placed in a refrigerator at 4°C. After 24 hours, the glass slide was taken out and then placed in a 365 nm double-sided ultraviolet lamp for crosslinking for 3 hours. The glass slide was then placed in a 0.1 M ZrOCl2·8H2O aqueous solution for 48 hours to complete the coordination crosslinking. The obtained hydrogel was further immersed in water for about 1 week, during which the water was changed several times. After the size was stabilized, the coated double network hydrogel coating was obtained.
[0054] Example 5
[0055] (1) 0.9 g of κ-carrageenan, 4.798 g of acrylamide, 6.285 g of dimethylpropylsulfonamide ethyl methacrylate, and 9 mL of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone solution (concentration of 1 × 10 -5 mol / mL), 90 μL triethylene glycol dimethacrylate solution (concentration 1×10 -4 mol / mL) was mixed with 21 mL of deionized water to obtain a mixed solution; the mixed solution was heated in a 70° C. water bath for 3 hours to obtain a uniform precursor solution;
[0056] (2) The precursor solution is coated on a polyvinyl chloride sheet, and after standing in the dark at room temperature for 1 hour, it is placed in a refrigerator at a temperature of 4°C, taken out after 28 hours, and then placed in a 365nm double-sided ultraviolet lamp for crosslinking for 3 hours, and then placed in a 0.5M ZrOCl2·8H2O aqueous solution for 36 hours to complete the coordination crosslinking. The obtained hydrogel is further immersed in water for about 1 week, during which the water is changed several times, and the coated double network hydrogel coating is obtained after the size is stable.
[0057] Example 6
[0058] (1) 0.9 g of κ-carrageenan, 4.478 g of acrylamide, 7.542 g of 3-[N,N-diethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]ethane-1-carboxylic acid inner salt, and 9 mL of 2,2'-azobisisobutylamidine dihydrochloride solution (concentration of 1 × 10 -5 mol / mL), 90 μL of ethylene glycol dimethacrylate solution (concentration of 1×10 -4 mol / mL) was mixed with 21 mL of deionized water to obtain a mixed solution; the mixed solution was heated in a 70° C. water bath for 3 hours to obtain a uniform precursor solution;
[0059] (2) The precursor solution was coated on a glass slide, and allowed to stand at room temperature in the dark for 1 hour, and then placed in a refrigerator at 4°C. After 24 hours, the precursor solution was taken out and then placed in a 365 nm double-sided ultraviolet lamp for crosslinking for 3 hours. The precursor solution was then placed in a 0.2 M ZrOCl2·8H2O aqueous solution for 46 hours to complete the coordination crosslinking. The obtained hydrogel was further immersed in water for about 1 week, during which the water was changed several times. After the size was stabilized, the coated double network hydrogel coating was obtained.
[0060] Example 7
[0061] (1) 0.9 g of κ-carrageenan, 4.478 g of acrylamide, 7.542 g of dimethylpropyl sulfonamide ethyl methacrylate, and 12 mL of a photoinitiator 2-hydroxy-2-methyl-1-phenyl ketone solution (concentration of 1 × 10 -5 mol / mL), 90 μL N,N'-methylenebisacrylamide solution (concentration of 1×10 -4 mol / mL) was mixed with 18 mL of deionized water to obtain a mixed solution; the mixed solution was heated in a 70° C. water bath for 3 hours to obtain a uniform precursor solution;
[0062] (2) The precursor solution was coated on a glass slide, and allowed to stand at room temperature in the dark for 1 hour, and then placed in a refrigerator at 4°C. After 24 hours, the glass slide was taken out and then placed in a 365 nm double-sided ultraviolet lamp for crosslinking for 3 hours. The glass slide was then placed in a 0.1 M ZrOCl2·8H2O aqueous solution for 48 hours to complete the coordination crosslinking. The obtained hydrogel was further immersed in water for about 1 week, during which the water was changed several times. After the size was stabilized, the coated double network hydrogel coating was obtained.
[0063] Example 8
[0064] (1) 0.9 g of κ-carrageenan, 4.478 g of acrylamide, 7.542 g of dimethylpropyl sulfonamide ethyl methacrylate, and 9 mL of a photoinitiator 2-hydroxy-2-methyl-1-phenyl ketone solution (concentration of 1 × 10 -5 mol / mL), 135 μL N,N'-methylenebisacrylamide solution (concentration of 1×10 -4 mol / mL) was mixed with 21 mL of deionized water to obtain a mixed solution, and the mixed solution was heated in a 70° C. water bath for 3 hours to obtain a uniform precursor solution;
[0065] (2) The precursor solution was coated on a glass slide, and allowed to stand at room temperature in the dark for 1 hour, and then placed in a refrigerator at 4°C. After 24 hours, the glass slide was taken out and then placed in a 365 nm double-sided ultraviolet lamp for crosslinking for 3 hours. The glass slide was then placed in a 0.1 M ZrOCl2·8H2O aqueous solution for 48 hours to complete the coordination crosslinking. The obtained hydrogel was further immersed in water for about 1 week, during which the water was changed several times. After the size was stabilized, the coated double network hydrogel coating was obtained.
[0066] Comparative Example 1
[0067] (1) 0.9 g of κ-carrageenan, 6.3972 g of acrylamide, and 9 mL of 2-hydroxy-2-methyl-1-phenylmethanone solution (concentration of 1 × 10 -5 mol / mL), 90 μL N,N'-methylenebisacrylamide solution (concentration of 1×10 -4 mol / mL) was mixed with 21 mL of deionized water to obtain a mixed solution; the mixed solution was heated in a 70° C. water bath for 3 hours to obtain a uniform precursor solution;
[0068] (2) The precursor solution was coated on a glass slide, and allowed to stand at room temperature away from light for 1 hour, and then placed in a refrigerator at 4°C. After 24 hours, the glass slide was taken out and then placed in a 365 nm double-sided ultraviolet lamp for crosslinking for 3 hours. The glass slide was then placed in a 0.1 M ZrOCl2·8H2O aqueous solution for 48 hours to complete the coordination crosslinking. The obtained hydrogel was further immersed in water for about 1 week, during which the water was changed several times. After the size was stabilized, the coated double network hydrogel coating was obtained.
[0069] Comparative Example 2
[0070] 1.081 g of acrylic acid, 0.0168 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, and 0.78 mL of N,N'-methylenebisacrylamide solution (concentration of 1 × 10 -4 mol / mL) was mixed with 5 mL of deionized water to obtain a mixed solution; the solution was injected into the middle of the mold using a syringe, and irradiated under a 365 nm ultraviolet lamp for half an hour to obtain a first network hydrogel (PAA);
[0071] 6.98 g of dimethylpropylsulfonamide ethyl methacrylate, 0.014 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, and 0.65 mL of N,N'-methylenebisacrylamide solution (concentration of 1×10 -4 mol / mL) was mixed with 25 mL of deionized water to obtain a mixed solution; then the prepared first network hydrogel PAA was immersed in the above mixed solution, immersed in the dark at 4°C for 16 hours, taken out and sandwiched between two glass plates, and irradiated under a 365 nm ultraviolet lamp for half an hour to obtain an interpenetrating network hydrogel.
[0072] Sample analysis
[0073] The hydrogel coatings prepared in the examples and comparative examples were subjected to tensile property tests, water content tests, friction tests, anti-bacterial adhesion tests, and anti-protein adsorption tests. The test methods are as follows:
[0074] (1) Tensile performance test
[0075] Use a cutter to cut out several dumbbell-shaped specimens with a neck length of 12 mm and a width of 2 mm from the sheet hydrogel sample (the thickness of the specimen was measured by a thickness gauge before the test, which was about 1.2 mm), wipe off the surface moisture, and then immediately perform a tensile test on the specimen, and record the fracture stress, fracture strain, and Young's modulus. Test instrument: universal electronic material testing machine (Instron 3343, USA), test temperature: room temperature (about 25°C), tensile speed: 100 mm min -1 , sensor accuracy: 50N.
[0076] (2) Moisture content test
[0077] Cut a sample from the hydrogel sample at swelling equilibrium, wipe off the surface moisture, and weigh the initial weight; after drying in an oven, weigh the weight of the dry hydrogel; calculate the percentage of the difference between the initial weight and the dry hydrogel weight to the initial weight, that is, the water content.
[0078] (3) Friction test
[0079] The sample was bonded to the fixture (flat plate, 20 mm in diameter) of a DHR rheometer (TA Instruments, USA). The normal stress was kept at 1 N, and the test was performed under set conditions such as shear rate and temperature.
[0080] (4) Antibacterial adhesion test
[0081] The experiment selected Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) as representatives, and the hydrogel samples were immersed in the culture solution of the two bacteria. After a period of time, the bacterial adhesion on the hydrogel surface was observed. Each sample was coated on three substrates as parallel samples, and the fluorescence photos were obtained under a fluorescence microscope (Thermo Fisher Scientific, EVOS FL Auto 2) with a magnification of 100 times.
[0082] (5) Anti-protein adsorption test
[0083] Phosphate buffer solution (PBS, concentration of 10mmol / L, pH=7.4, I=150mmol / L) was prepared, and a series of concentrations of bovine serum albumin (BSA) were prepared with PBS solution, and tested by UV spectrometer (Varian / cary50) using Bradford method to obtain the relationship curve between the intensity of characteristic UV absorption peak and solution concentration (Note: the characteristic UV absorption peak of BSA is located at about 277nm, and the special UV absorption peak after labeling with Coomassie brilliant blue dye is at about 595nm); then the test samples were immersed in PBS solution with a concentration of 1g / L BSA, and placed in a constant temperature oscillation environment (oscillation frequency: 150rpm, temperature: 37℃, time: 24h). The protein adsorption on the sample surface was characterized according to the change in the intensity of the characteristic UV absorption peak of the test sample before and after immersion in the protein solution.
[0084] The tensile properties test, water content test, and friction test results of the hydrogel coatings prepared in the examples and comparative examples are shown in Table 1:
[0085] Table 1 Performance test results of hydrogel coatings prepared in Examples and Comparative Examples
[0086]
[0087] From the results in the above table, it can be seen that at 25°C, the mechanical properties of the coated double network hydrogel coating in swelling equilibrium in deionized water are excellent, with a breaking stress of 1.98MPa, a breaking elongation of 1171%, and a Young's modulus of 2.03MPa. The friction force of the substrate with the coated double network hydrogel coating in water was tested by a rotational rheometer, and the friction force of the substrate was reduced by more than 45% compared with the initial substrate friction force. The representative results of the adsorption and adhesion of the coated double network hydrogel coating prepared in the embodiment to Escherichia coli, Staphylococcus aureus and bovine serum albumin are shown in the figure. Figure 1-3 As shown, the coated double-network hydrogel coating has a very low number of adsorbed bacteria and proteins, indicating that it has excellent antibacterial and anti-protein effects. If the zwitterionic monomer is not used as the second network monomer, the hydrogel coating has a high number of adsorbed bacteria and proteins, and the antibacterial and anti-protein effects are poor.
[0088] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. Application of a coated double network hydrogel coating in the field of marine antifouling, characterized in that: The method for preparing the coating type double network hydrogel coating comprises the following steps: (1) mixing κ-carrageenan, a second network monomer, a photoinitiator, a crosslinking agent and water to obtain a mixed solution, and heating the mixed solution at 60-90° C. for 2-6 hours under light-proof conditions to obtain a uniform precursor solution; (2) coating the precursor solution onto a substrate, refrigerating and standing under light-proof conditions at a temperature of 0-8° C. for a period of 12-36 hours, taking it out and subjecting it to UV light crosslinking treatment and metal ion solution immersion coordination crosslinking treatment, and further immersing the obtained hydrogel in water to obtain the coated double network hydrogel coating after the size is stabilized; The second network monomer includes an acrylic monomer and a zwitterionic monomer; the acrylic monomer is acrylamide, acrylic acid, methacrylamide or methacrylic acid; the zwitterionic monomer is dimethylpropylsulfonamide ethyl methacrylate, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-phosphate inner salt, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]ethane-1-carboxylic acid inner salt, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt or 3-[N,N-diethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]ethane-1-carboxylic acid inner salt; In step (1), the mass ratio of the κ-carrageenan to the second network monomer is 0.075-0.15:1; in the second network monomer, the molar fraction of the propylene monomer is 60-99%, and the molar fraction of the zwitterionic monomer is 1-40%; the molar ratio of the second network monomer, the photoinitiator and the crosslinking agent is 1:5×10 -4 -1.5×10 -3 :5×10 -5 -1.5×10 -4 ; The coated double network hydrogel coating is made of κ-carrageenan, metal ions, acrylic monomers, zwitterionic monomers, photoinitiators, and crosslinking agents; wherein, after the κ-carrageenan undergoes a sol-gel transition, it forms a first crosslinking network through coordination with the metal ions, and the acrylic monomers and zwitterionic monomers form a second crosslinking network through free radical polymerization under the action of the photoinitiator and the crosslinking agent; the coated double network hydrogel coating has a double network structure formed by the first crosslinking network and the second crosslinking network interpenetrating each other.
2. The use according to claim 1, characterized in that: The metal ion is Zr 4+ .
3. The use according to claim 1, characterized in that: The photoinitiator is a water-soluble photoinitiator, selected from at least one of 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxy-cyclohexyl-phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,2'-azobisisobutylamidine dihydrochloride, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone; The crosslinking agent is a water-soluble crosslinking agent, selected from at least one of N,N'-methylenebisacrylamide, N,N'-vinylbisacrylamide, hexamethylenebisacrylamide, ethylene glycol diacrylate, dipropylene glycol diacrylate, triethylene glycol dimethacrylate and ethylene glycol dimethacrylate.
4. The use according to claim 1, characterized in that: The conditions for metal ion solution immersion coordination crosslinking are: the metal ion solution is 0.05-0.5M Zr 4+ The solution is soaked for 36-60 hours.
Citation Information
Patent Citations
Preparation method of high-flexibility amphoteric ionic hydrogel
CN105295073A
Preparation method and application of high-performance and low-friction nano composite hydrogel
CN115260529A
Preparation method and application of high-strength, anti-fouling and anti-drag soft hydrogel coating
CN108727937A
Preparation method of metal coordination enhanced double-network hydrogel
CN109485792A